Training of the Curriculum (K-13) e-Rapor Information System for the Teachers of Senior High School - Sabam Parjuangan; M Dwiyan Aditiya; Nurfiana Nurfiana (Jurnal Pengabdian Kepada Masyarakat (Indonesian Journal of Community Engagement), 2020)
The curriculum transformation of primary and secondary education in Indonesia had stimulated the transformations movement of technology. One of these transformations was in the form of the student grade report (e-rapor) in Indonesian schools. This transformation required primary and secondary school teachers to be adapted to use information technology. The efforts to answer this transformation were carried out through the technical guidance to provide training for teachers of Sekolah Menengah Atas (SMA) and Sekolah Menengah Kejuruan (SMK) Persada Bandar Lampung by filling out this e-Rapor. This training was carried out through several main materials i.e., the application installation, the application troubleshooting, and the use of e-Rapor. This training was implemented in 3 days. Moreover, the next training was also conducted to deal with some of the arising problems after the technical guidance was conducted. This technical guidance was attended by 27 teachers. This technical guidance was implemented by delivering material, conducting the simulation, and doing discussion. The result of this technical guidance was analyzed quantitatively through observations and discussions. It showed that all technical guidance participants were able to fill out the e-Rapor system according to their respective roles after the technical guidance implementation on filling out the e-Rapor.